Long-term real-world effectiveness of allergy immunotherapy in patients with allergic rhinitis and asthma: Results from the REACT study, a retrospective cohort study. - Benedikt Fritzsching (Elsevier, 2022)
Summary: Background: Allergen immunotherapy (AIT) is the only causal treatment for respiratory allergy. Long-term real-life effectiveness of AIT remains to be demonstrated beyond the evidence from randomised controlled trials (RCTs). Methods: REACT (Real world effectiveness in allergy immunotherapy) is a retrospective cohort study using claims data between 2007 and 2017. Study eligibility was a confirmed diagnosis of allergic rhinitis (AR), with or without asthma, and AIT. To ensure comparable groups, AIT-treated subjects were propensity score matched 1:1 with control subjects, using characteristic and potential confounding variables. Outcomes were analysed as within (pre vs post AIT) and between (AIT vs control) group differences across 9 years of follow-up (ClinicalTrial.gov: NCT04125888). Findings: 46,024 AIT-treated subjects were matched with control subjects and 14,614 were included in the pre-existing asthma cohort. AIT-treated subjects were 29·5 (16·3) years and 53% were male. Compared to pre-index year, AIT was consistently associated with greater reductions compared to control subjects in AR and asthma prescriptions, including both asthma controller and reliever prescriptions. Additionally, the AIT group had significantly greater likelihood of stepping down asthma treatment (P <0·0001). In addition to the reduction in asthma treatment in the AIT group, a greater reduction in severe asthma exacerbations was demonstrated (P<0·05). Reductions in pneumonia with antibiotic prescriptions, hospitalisations, and duration of inpatients stays were all in favour of AIT. Interpretation: The study extends the existing RCT evidence for AIT by demonstrating longer-term and sustained effectiveness of AIT in the real world. Additionally, in patients with concurrent asthma, AIT was associated with reduced likelihood of asthma exacerbations and pneumonia. Funding: The study was funded by ALK A/S.